COVID-19: How Nuclear Medicine Can Provide A Differential Diagnosis In A Very Dubious Case - De Feo, Maria S.; Frantellizzi, Viviana; De Vincentis, Giuseppe (Coronaviruses, 2021)
Background: We present the case of a 55-year-old woman, admitted to the Infectious Disease Department of Policlinico Umberto I, Rome, in mid-March 2020, with suspicion of COVID-19 infection. Objective: The rRT-PCR was negative, and the following CT scan, performed to exclude false-negative results and help diagnosis, was inconclusive. Methods: It was decided to submit the patient to a 99mTc-HMPAO-labelled leukocyte scan. Results: This exam led to the diagnosis of infective endocarditis. Conclusion: In the present pandemic scenario, 99mTc-HMPAO-labelled leukocyte scan represents a reliable imaging technique for differential diagnosis with COVID-19 in patients with confusing clinical signs, possible false-negative rRT-PCR results, and inconclusive CT scan.
Keywords: SARS-CoV-2